A Web Based System for Easy and Secured Managing Process of University Accreditation Information - Benjamin Kommey; Francis Gyimah; Jerry John Kponyo; Samuel Ato Andam-Akorful (Faculty of Engineering and Technology, Sampoerna University, 2022)
Higher institutions run various programs. These programs must be authorized, in other words accredited by a National Institution for accreditation to ensure quality and standards. This research paper aims to provide a convenient way of accreditation for the various programs in universities or institutions of higher learning. The College of Engineering at the Kwame Nkrumah University of Science and Technology (KNUST) was used as a case study. Using the client-server model, a web-based, very flexible, and well secured accreditation management software was designed to address most of the challenges faced with manual accreditation process of the College of Engineering. The system provides a central database where all accreditation related information of the various programs is stored for easy access and modification by authorized personnel. A secured link and robust access control via authentication were implemented and a user management system was integrated. The system was tested and resulted encouraging outcomes, with some further works are recommended in the future to improve the features of the system.